PENGARUH PENERAPAN PROSEDUR HIRARC TERHADAP KESELAMATAN KERJA DI KILANG MINYAK - Faiz Agung Luthfiansyah; Puteriyani Khairunisa; Dena Yulianti; Abdurrozzaq Hasibuan (CV. KAMPUS AKADEMIK PUBLISHING, 2025)
Occupational safety in oil refineries is a critical concern due to the high-risk environment involving physical, chemical, mechanical, ergonomic, and psychosocial hazards. This study aims to analyze the impact of implementing the HIRARC method (Hazard Identification, Risk Assessment, and Risk Control) on improving workplace safety in refinery operations. A descriptive qualitative approach was employed using secondary data from various previous studies. The hazard identification process revealed 56 potential hazards, which were classified and assessed based on risk levels using a risk matrix. Risks were categorized from low to extreme, with control efforts focused on high and extreme levels. Control strategies included elimination, substitution, engineering controls, administrative controls, and the use of personal protective equipment (PPE). The systematic application of HIRARC proved effective in reducing accident rates and strengthening safety culture. Furthermore, integrating the Lean Safety approach with HIRARC was found to significantly lower overall risk levels. These findings indicate that optimal HIRARC implementation can serve as a strategic solution to mitigate occupational accident risks in the oil and gas industry.